Development of interactive e-modules to improve students’ scientific literacy abilities: A literature review - Herlina, Elin; Abidin, Zaenal (Universitas Wiralodra, 2024)
This research aims to investigate the development of the interactive e- Module in the context of improving students' scientific literacy skills. The approach employed in this research involved a systematic literature review, detailing the latest developments from 2019 to 2023 in the use of interactive e-Modules to enhance scientific literacy among students in Indonesia and abroad. The Meta-synthesis techniques were applied in this research. The samples utilized were sourced from 2019-2023 and were retrieved from international journals Google Scholar, Scopus, and Eric with the keyword